Evaluation of The Use of Garlic (Allium sativum) in Enhancing Nonspecific Immune Response and Growth of Nile Tilapia (Oreochromis niloticus) - Marentek, Gercyana; Manoppo, Henky; Longdong, Sammy N.J (Universitas Sam Ratulangi, 2013)
The objective of this research was to examine the effect of garlic (Allium sativum) at different doses on nonspecific immune response and growth of nile tilapia (Oreochromis niloticus). Experimental fish was nile tilapia measuring 8-15 cm with an average weight of 10.4 g per individual. Before used in the experiment, fish were reared in fiber tank for two weeks for acclimatization. After acclimatization, the fish were moved into glass aquarium (50 cm x 30 cm x 30 cm) at the density of 15 fish/aquarium. Each aquarium was equipped with aerator. Five doses of garlic as treatments used in this research consisted of A= 0 g/kg diet, B= 10 g/kg, C= 20 g/kg, D= 30 g/kg and E= 40 g/kg. Fish was fed experimental diet at a dose of 5% of body weight per day, twice a day at 08.00 and 17.00. Data collected at the end of the experiment included immune parameters (TLC and phagocytosis activity) and growth of fish. ANOVA was used to evaluate the effect of treatments on immune response and growth of fish while Duncan Test was used to evaluate the different effect between treatments. Research result showed that after four weeks of feeding, TLC of fish fed diet supplemented with garlic significantly different (p<0,01) as compared to that of control fish. The highest number of TLC was observed at treatment C (15.413x107 cell.ml-1) followed by treatment B (15.39x107 cell.ml-1), D (13,920 x 107 cell.ml-1), E (13,582 x 107 cell.ml-1) and A (12,195 x 107 cell.ml-1). TLC of fish in treatment C was different significantly compared to control as well as to other treatments. Phagocytosis activity of fish in treatment C also increased significantly (p<0,01) compared to control. The highest PA was achieved in treatment C and then treatment B, D, E and A. Growth of fish in treatment C was different significantly compared to control fish as well as other treatments. As conclusion, oral administration of garlic at 20 g/kg diet could enhance nonspecific immune response and growth of nile tilapia. Key words: Garlic, Immune response, Total leukocyte count , Phagocytosis activity, Growth